Effect of replacing concentrate diet with oat brewery waste on enteric methane emissions, nutrients intake, digestibility and compositional and functional abundances of rumen microbiota in growing male sheep - Prajapati, Vedant Jayeshkumar; Mohapatra, Archit; Trivedi, Shraddha; Malik, Pradeep Kumar; Kolte, Atul Purushottam; Suganthi, Umaya R.; Victor, Tsuma; Ahasic, Elena; Sahoo, Artabandhu; Bhatta, Raghavendra (Frontiers in Microbiology, 2026)
A study was carried out to examine the impact of two levels of oat brewery waste (OBW) on enteric methane (CH4) emissions, feed intake, rumen fermentation, rumen microbiota, and growth performance. A total of 21 male Bannur sheep in their growth phase were randomly assigned to three groups using a completely randomized design, receiving diet containing three levels of OBW: 0% (control group; C), 20% (T1), and 30% (T2). To achieve these levels in the diet, the concentrate was accordingly replaced with OBW (w/w). The finger millet straw and concentrate were offered separately, maintaining the concentrate to roughage ratio of 50:50. Aflatoxin B1 had no presence in the fresh OBW. The dry matter intake (g/day) in T2 group was significantly lower (P < 0.05) as compared to C and T1 groups. Sheep in T1 and T2 groups showed significantly lower (P < 0.05) daily CH4 emissions, decreased by 14%−15.5% as well as lower total energy loss (P < 0.05) compared to the group C. The feeding of OBW resulted in a notable decrease (P < 0.05) in volatile fatty acid (VFA) concentration (mmol) in the group T2 as compared to C. A noteworthy reduction (P < 0.05) in the total counts of protozoa and Entodinimorphs was observed at the 30% OBW (T2). The findings indicated that feeding OBW did not negatively affect the growth performance of sheep. Metatranscriptomic data from 15 individual animals, 5 from each group indicated that Bacteroidota was the predominant phylum, making up approximately 40% of the rumen microbiota. Their compositional abundance showed a significant decrease with the feeding of OBW at specified levels in present study. Conversely, there was an increase in the compositional abundance of Pseudomonadota in the test groups. Though the feeding of oat brewery waste in short-term (90 days) did not restructure the archaeal community composition, nevertheless it significantly affects the metabolic capabilities of the methylotrophic methanogens. The findings indicated that the OBW at a level of 20% in the diet led to a significant reduction (P < 0.05) in daily enteric CH4 emissions while not affecting feed intake, digestibility, or growth performance. Replacing concentrate with OBW at a level of 20% of diet can lead to monetary benefits while also providing the added advantages of lowering CH4 emissions.